2005
DOI: 10.1038/sj.jcbfm.9600142
|View full text |Cite
|
Sign up to set email alerts
|

Heat Acclimation Increases Hypoxia-Inducible Factor 1α and Erythropoietin Receptor Expression: Implication for Neuroprotection after Closed Head Injury in Mice

Abstract: Experimental evidence indicates that long-term exposure to moderately high ambient temperature (heat acclimation, HA) mediates cross-tolerance to various types of subsequently applied stress. The transcriptional activator hypoxia-inducible factor 1 (HIF-1) has been implicated in playing a critical role in HA. It also regulates the expression of Erythropoietin (Epo), whose neuroprotective effects have been shown in a variety of brain injuries. The aim of the present study was to examine whether HA exerts a bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
83
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(96 citation statements)
references
References 45 publications
11
83
0
Order By: Relevance
“…Previously, we have shown that HA induces a neuroprotective effect in both rats and mice, reflected by reduced tissue edema formation and improved functional recovery during the initial 24 to 72 h after impact (Shein et al, 2005;Shohami et al, 1994). Our current findings further expand these previous ones, and show that enhanced recovery of function by HA Figure 3 Effect of heat acclimation and closed head injury (CHI) on Bcl-xL and Bad mRNA levels.…”
Section: Discussionsupporting
confidence: 83%
“…Previously, we have shown that HA induces a neuroprotective effect in both rats and mice, reflected by reduced tissue edema formation and improved functional recovery during the initial 24 to 72 h after impact (Shein et al, 2005;Shohami et al, 1994). Our current findings further expand these previous ones, and show that enhanced recovery of function by HA Figure 3 Effect of heat acclimation and closed head injury (CHI) on Bcl-xL and Bad mRNA levels.…”
Section: Discussionsupporting
confidence: 83%
“…Such a model mimics several pathophysiological characteristics of human focal cortical contusion (Nag, 1996) and produces a reproducible, demarcated lesion to the neocortex that allows evaluation of the efficacy of compounds with a neuroprotective potential (Hortobagyi et al, 2000). The present findings extend previous work by showing that rHuEPO significantly reduces brain injury and improves neurological recovery following traumatic insults (Brines et al, 2000;Lu et al, 2005;Ozturk et al, 2005;Shein et al, 2005;Siren et al, 2006;Verdonck et al, 2007;Yatsiv et al, 2005). In particular, rHuEPO administration improved both functional and cognitive recovery of the rats with an effect that was significantly shown since the early stage after TBI and lasted for 15 days.…”
Section: Discussionsupporting
confidence: 78%
“…Although the role of EPO as a neuroprotectant has been studied extensively in a wide range of in vitro and in vivo models of brain injury, up to date, there are only few studies evaluating the effect of rHuEPO after experimental TBI (Brines et al, 2000;Lu et al, 2005;Ozturk et al, 2005;Shein et al, 2005;Siren et al, 2006;Verdonck et al, 2007;Yatsiv et al, 2005) and none has used a cryogenic injury paradigm. Neurobehavioral improvement after EPO administration has been reported in other studies where different models of brain injury were used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although peripherally administered recombinant human Epo (rhEpo) has shown to penetrate the blood-brain barrier and reduce brain injury (4, 17), its potential neuroprotective efficacy in an in vivo model of experimental TBI has been rarely investigated (4, 26,30,31). In addition, there are numerous studies regarding the widespread efficacy of rhEpo in injury models of spinal cord (14, 18) and subarachnoid hemorrhage (15,17,33) promoting the role of Epo as an essential mediator of protection in the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%